Teaching reading comprehension and vocabulary using memes - Cordova, Monique; Badanoy, Edgar; Genegaboas, Isabelo (Frontiers in Education, 2025)
In the digital age, memes have emerged as valuable tools for 21st-century learning. This study investigates how meme-based instruction can enhance learners’ reading comprehension and vocabulary development. Using an explanatory sequential mixed-methods design, the study employed a quasi-experimental approach with control and experimental groups. Quantitative data were gathered through pretest and posttest to measure reading comprehension and vocabulary performance, followed by focus group discussions to explore learners’ perceptions and experiences. The findings revealed a slight improvement in reading comprehension and a more pronounced enhancement in vocabulary among learners exposed to meme-based instruction. Learners also reported positive perceptions of memes, emphasizing their ability to motivate engagement, evoke humor, promote critical thinking, and facilitate deeper comprehension. These results underscore the potential of memes as innovative pedagogical tools that make learning more engaging and effective.